Torn away - Brown, Jennifer, 1972- (Little, Brown and Company, 2014)
In the aftermath of a tornado that has devastated her hometown of Elizabeth, Missouri, sixteen-year-old Jersey Cameron struggles to overcome her grief as she is sent to live with her only surviving relatives.